Role of Rewards Management on Employee Performance in the Banking Sector. - Alex, Kanyesime (Uganda Management Institute, 2019)
The study topic was to examine the role of rewards management on employee performance in the banking sector, using a case study of centenary bank. The study was conducted basing on the following objectives; to investigate the impact of fringe benefits on employee performance, to examine the contribution of pay incentives on employee performance, to establish the contribution of job satisfaction on employee performance, to establish the influence of sense of belongingness on employee performance and to establish the effect of organization policy on the performance of employees in the banking sector in Uganda. The research design was a case study design which adopted both qualitative and quantitative approaches. Simple random sampling technique and purposive sampling were used to select a sample size of 129 respondents of which it was composed of management members and employees. Data collection methods used was questionnaire and interviews. Data were later processed, analyzed, interpreted, discussed and presented to come up with conclusions and recommendations of the study. The findings of the study were that; pay incentives improve employee performance, there is high level employee belongingness and recognition which was attributed to improved performance of employees, employees were satisfied with their jobs they held which contributed to the improved performance of employees, and, the organization’s policies were friendly which greatly improved on the performance of employees in the banking sector in Uganda. The study concluded that; rewards which included pay incentives, fringe benefits, job satisfaction, employee recognition plus organizational policies influenced employee performance in centenary bank leading to effective utilization of resources, quality service delivery and meeting deadlines. The study recommended that; conducting a national drive and public sensitization about all the new services like internet banking, government intervention, employee training and development, extensive research and development, and, ensuring local community involvement in decision making like on the new services be introduced